Use of Personal Computer for Quality Teaching in Civil Engineering - Bhosale, M. M.; Ronghe, G. N. (Journal of Engineering Education Transformations, 1990)
At present class room teaching is adopted in Engineering without consideration about assimilation by students. Pace of learning of each student is different especially when variety of subjects are considered. Ideally it should be possible to teach at the pace of individual student. To achieve this, extensive use of computer is suggested to make good deficiency arising out of insufficient number of teachers. Paper outlines drawbacks of the existing teaching methodology and how cheaper effective solution can be obtained by use of personal computers.